Informal Leadership Learning on the Journey to Headship: A Case Study of National Professional Qualification for Headship Participants in Malaysia - Singh, Gurcharan; Singh, Bishen (Universiti Putra Malaysia Press, 2018)
The current focus on school leader preparation around the world is based on the belief that school leaders make a difference in both effectiveness and efficiency of schooling. This study is part of an evaluative case study on the National Professional Qualification for Headship (NPQH) programme in Malaysia. It seeks to investigate the perceptions of ten incumbent secondary school principals who are graduates of the NPQH programme on the informal leadership learning they acquired from the time they graduated to the roles they played as principals. The study investigated informal leadership learning in the professional setting at school, professional setting outside school as well as leadership learning outside the professional setting. The findings of this qualitative inquiry point towards a great deal of informal leadership learning in the professional setting at school. Whilst informal leadership learning in the professional setting outside of school was reportedly derived from the active role played by the respondents themselves, very little leadership learning was acquired outside the professional setting. The implication of this study for the preparation of school heads in Malaysia is discussed and proposals made towards optimising the benefits of informal leadership learning for aspiring heads. (Abstract by authors)